Pendampingan Pengembangan Pemasaran UMKM Kerajinan Udeng Melalui Inovasi Digital Di Desa Munung Kecamatan Jatikalen Kabupaten Nganjuk - Umah, Yuli Choirul; Masrifatin, Yuni (STAI Miftahul ULa Nganjuk, 2023)
Munung Village is one of the Swakarya Villages Nganjuk Regency. This community service focused on developing marketing and preserving cultural products in Munung Village. The target program of this community service activity focused on the economic sector, namely Udeng Craft by UMKN. Udeng in Javanese is a cloth head covering that is part of men's daily equipment. Udeng is a headband that is often worn with certain traditional clothing and is also used as a complement to the groom's clothing. This community service program research used the Asset Based Community Development (ABCD) approach. This approach emphasized investment in assets in society which was seen as community empowerment activities. The aim of this community service assistance was to improve marketing and utilize the assets of UMKM in Munung Village, Jatikalen District, Nganjuk Regency, namely by assisting in the development of marketing of Udeng craft by UMKM through digital innovation in Munung Village, Jatikalen District, Nganjuk Regency. After developing marketing through social media and online shopping platforms, Udeng Miza has started an increase in sales. Which usually sells 20 pcs a week, then it could reach more than 40 pcs a week, both online and offline shopping or directly to the location on the Google Map application